1991
DOI: 10.1136/jnnp.54.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow reactivity to hypercapnia in strictly unilateral carotid disease: preliminary results.

Abstract: To show a relationship between degree of carotid arterial stenosis and cerebral blood flow reactivity (RES%) to induced hypercapnia, fluorine-18-fluoromethane and positron emission tomography (PET) was used to study 18 We have studied 18 patients who have strictly unilateral extracranial carotid arterial disease using positron emission tomography (PET), fluoromethane ('8FCH3) and CBF reactivity to induced hypercapnia. In this preliminary study we aimed to non-invasively study the physiological effect of varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…38,[61][62][63][64][65][66][67][68][69][70][71][72][73] In 1 study only 70 did the authors explicitly state that associated IWS infarcts were excluded, which is, however, partly explained by the fact that interest in IWS infarcts is relatively recent. For instance, in 1 early PET study, 67 all symptomatic patients had IWS infarcts as well.…”
Section: Studies That Specifically Assessed the Pathophysiology Of Cwmentioning
confidence: 99%
See 1 more Smart Citation
“…38,[61][62][63][64][65][66][67][68][69][70][71][72][73] In 1 study only 70 did the authors explicitly state that associated IWS infarcts were excluded, which is, however, partly explained by the fact that interest in IWS infarcts is relatively recent. For instance, in 1 early PET study, 67 all symptomatic patients had IWS infarcts as well.…”
Section: Studies That Specifically Assessed the Pathophysiology Of Cwmentioning
confidence: 99%
“…The observed hemodynamic abnormalities were reported to predominantly affect the anterior watershed (AWS) 63,64,66,68,69,72 more frequently than the posterior watershed (PWS). 38,67 Four studies assessed the CWS hemodynamics before and after successful revascularization, either extracranial-intracranial bypass 38,62 or carotid endarterectomy, 66,72 and each reported complete or partial resolution of the previously observed perfusion abnormalities.…”
Section: Studies That Specifically Assessed the Pathophysiology Of Cwmentioning
confidence: 99%
“…Because the vascular responsiveness to vasodilator in the brain with insufficient cerebral perfusion pressure is reduced by autoregulatory vasodilation , hypercapnia can be used to estimate cerebral perfusion reserve in occlusive cerebrovascular disease (Herold et al, 1988;Levine et al, 1991;Kuwabara et al, 1997).…”
mentioning
confidence: 99%
“…12, 13 Nishimura et al found that CBF did not decrease during trimethaphan-induced hypotension (mean systemic arterial BP reduction 15 mm Hg) when CPR was Ϸ5%, whereas CBF was reduced by 0% to 5% and 5% to 10% when CPR was Ϸ4% and 3%, respectively. 18 Although vasoreactivity to PaCO 2 may not fully reflect the autoregulatory perfusion reserve in response to changes of perfusion pressure, the improved CPR from 3.7% to 4.8%/ mm Hg during chronic ACE inhibitor therapy seems to represent the recovery of autoregulatory protection against hypotension, as observed in experimental [2][3][4] and clinical studies.…”
Section: Hatazawa Et Al Perindopril Improves Cerebral Perfusion Resermentioning
confidence: 99%
“…Two arterial blood samples were taken, 1 at the beginning and 1 at the end of scanning, for measurement of PaCO 2 . The cerebral perfusion reserve (CPR) was defined as the percent CBF response to hypercapnia and hypocapnia, which was calculated as follows: [11][12][13] CPR (%CBF/mmHg)ϭ100ϫ(CBF hyper ϪCBF hypo )/CBF rest ϫ1/(PaCO 2hyper ϪPaCO 2hypo ), where "hyper," "hypo," and "rest" denote measurement during hypercapnia, hypocapnia, and under resting conditions.…”
Section: Cerebral Perfusion Reservementioning
confidence: 99%